Male breast cancer in Iceland - Jonasson, J G; Agnarsson, B A; Thorlacius, S; Eyfjord, J E; Tulinius, H (John Wiley & Sons Inc, 2010)
To access publisher full text version of this article. Please click on the hyperlink in Additional Links field All malignant tumours of the male breast diagnosed in Iceland during the 40-year period 1955-1994 were studied with regard to histological classification, tumour grading and flow cytometric analysis. Of 31 malignant tumours diagnosed, 29 were primary breast carcinomas. Male breast carcinoma constitutes 1% of all breast malignancies in Iceland and 0.25% of all malignant tumours in males. About 80% of the male breast carcinomas were diagnosed during the latter half of the study period. The mean age of the patients was 66.3 years and the left-to-right ratio was 1.9:1.0. Right-sided tumours appeared to be more aggressive. The mean tumour size was 2.6 cm. The vast majority of the carcinomas (79%) were of the infiltrating ductal type. Of these 21.7% were grade I, 43.5% were grade II and 34.8% grade III. Papillary carcinomas made up 17% of the total. These occurred in slightly older patients than the infiltrating ductal carcinomas and were diploid tumours. In this study 57% of the tumours were found to be aneuploid, but nearly 70% of the invasive ductal carcinomas NOS were aneuploid. In general, the aneuploid tumours were larger, of higher average histological grade and had a higher mean S-phase value. The overall mean S-phase fraction was 7.2% which is similar to that found in female breast tumours in Iceland. It is concluded that male-to-female ratio of breast carcinoma in Iceland is similar to that found in other Western countries. The age-standardised incidence has increased considerably in the last 20 years, in contrast to the rates reported from most other countries. Papillary tumours are unusually common in Icelandic males.